WORK FROM HOME SATISFACTION DURING THE COVID-19 PANDEMIC OF OFFICERS IN THE OFFICE OF DEFENCE SERVICE COMMITTEE, SECRETARIAT DEPARTMENT, OFFICE OF THE PERMANENT SECRETARY FOR DEFENCE - limprasert, chanoknan; โกวงศ์, ศรีรัฐ (Thai Interdisciplinary and Sustainability Review, 2023)
The objectives of the research were 1) to study the level of job satisfaction while work from home during the COVID-19 pandemic of Officers in the Office of Defence Service Committee, Secretariat Department, 2) to compare job satisfaction while work from home during the COVID-19 pandemic according to the demographic factors, 3) to study the relationship between work-from-home related factor and job satisfaction while work from home during the COVID-19 pandemic. The results showed that the level of job satisfaction while work from home during the COVID-19 pandemic of Officers was high. The hypothesis testing revealed that the difference in education had different job satisfaction while work from home. In addition, work-from-home related factor had a moderate positive relationship with the job satisfaction while work from home.